2009
DOI: 10.1088/0953-8984/21/35/355007
|View full text |Cite
|
Sign up to set email alerts
|

In adatom diffusion on InxGa1−xAs/GaAs(001): effects of strain, reconstruction and composition

Abstract: By using density functional theory (DFT) calculations of the potential energy surface in conjunction with the analytical solution of the master equation for the time evolution of the adatom site distribution, we study the diffusion properties of an isolated In adatom on In(x)Ga(1-x)As wetting layers (WL) deposited on the GaAs(001). The WL reconstructions considered in this study are, listed in the order of increasing In coverage: c(4 × 4), (1 × 3), (2 × 3), α(2)(2 × 4) and β(2)(2 × 4). We analyze the dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…However, the InAs QDs are formed with a highly strained interface between QD and underlying layer. This triggers the surface migration of adatoms than volume enhancement, which is required for the relaxation of additional surface strain …”
Section: Resultsmentioning
confidence: 99%
“…However, the InAs QDs are formed with a highly strained interface between QD and underlying layer. This triggers the surface migration of adatoms than volume enhancement, which is required for the relaxation of additional surface strain …”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been also done for surface structures and In adatom diffusion on the InAs/GaAs(001) from theoretical viewpoints [71][72][73][74][75][76][77][78][79]. For the InAs/GaAs (111), Yamaguchi et al reported experimental measurements using STM on the mechanisms of strain relaxation in InAs/GaAs(111)A heteroepitaxy to propose a possible model for the resulting semicoherent interface structure [80].…”
Section: Inas On Gaasmentioning
confidence: 99%
“…In principle, this is also possible for semiconductor systems, but surface reconstrutions and the exact atomic structure at the step edge make this a more complicated exercise. DFT has also successfully been used to study the strain dependence of adatom diffusion during epitaxial growth, for both metallic 9,10 as well as semiconductor systems [11][12][13][14] . But surprisingly, very little is known about the strain dependence of other microscopic parameters during growth, such as diffusion along an island edge, detachment from an island edge, or dissolution of a small island.…”
Section: Pacs Numbersmentioning
confidence: 99%